2017
DOI: 10.3386/w23719
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Peer Effects Using Genetic Data

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w23719.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Social-genetic effects, also called "indirect" genetic effects, refer to the influence of one organism's genotype on a different organism's phenotype (14,15). Social-genetic effects, which may take several forms (1), are accounted for in evolutionary theory (42,43) and have been observed among animals (15,(44)(45)(46)(47) and received some study in human siblings (14,48,49).…”
Section: Is the Social Genome Associated With An Individual's Phenotype?mentioning
confidence: 99%
“…Social-genetic effects, also called "indirect" genetic effects, refer to the influence of one organism's genotype on a different organism's phenotype (14,15). Social-genetic effects, which may take several forms (1), are accounted for in evolutionary theory (42,43) and have been observed among animals (15,(44)(45)(46)(47) and received some study in human siblings (14,48,49).…”
Section: Is the Social Genome Associated With An Individual's Phenotype?mentioning
confidence: 99%
“…3 Some interesting recent studies aim to address this challenge. Cutler and Glaeser (2010) exploit smoking bans at the workplace to study spousal smoking behavior; Fletcher and Marksteiner (2017) analyze spouses' behavior in clinical interventions to reduce individuals' smoking and alcohol consumption; and Cawley et al (2017) study eects across siblings in weight and obesity by instrumenting for a sibling's obesity using genetic risk scores. 1 multiplier: the eects cascade to siblings, stepchildren, sons and daughters in-law, and even close coworkers, who exhibit responses of the same order of magnitude as spouses.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of social genetic effects originated in evolutionary theory (Moore, Brodie, and Wolf 1997;Wolf et al 1998), and social genetic effects have been observed in animal populations (Petfield et al 2005;Bergsma et al 2008;Canario, Lundeheim, and Bijma 2017;Baud et al 2018). Social science is now beginning to study such effects in human populations; examples include among social peers (Sotoudeh, Conley, and Harris 2017;Domingue et al 2018), sibling pairs (Cawley et al 2017;Kong et al 2018), and parents and their children (Bates et al 2018;Kong et al 2018;Wertz et al 2018). The existence of within-family social genetic effects complicates attempts to derive causal estimates from GWAS.…”
Section: B the Problem Of Confoundingmentioning
confidence: 99%